How the Constitutional Court Secures the Future of Democracy in Indonesia: Case Study Regional Head Election Dispute Settlement - AHMAD, DR. SUFMI DASCO; ASRUN, DR. ANDI MUHAMMAD (The journal of contemporary issues in business and government, 2021)
The Implementation of direct local elections was a correction of the local elections with a system of direct appointment by the central government in Jakarta during the era of the 32-years New Order government led by President Suharto. In the Suharto era, regional head candidates submitted without a vice head of the region and should be one name. Such conditions as described above was due to the undemoractic political system. Local elections immediately after the Suharto government is part of the development of a democratic political system. Democratic political participation will bear a truly participatory political system and political stability. However, it is undeniable that the electoral system sometimes was colored with money politics, non-neutrality of election organizers and local officials and all forms of intidimation against other participants. In the past, the Constitutional Court has several times to disqualify the winner of the election for fraudulent practices systematic, structured and massive and ordered a re-election without the participation of the participants who cheat. That is the Constitutional Court's role in fostering democracy in the region.